2009
DOI: 10.1007/s11033-008-9440-z
|View full text |Cite
|
Sign up to set email alerts
|

Association study of a single nucleotide polymorphism in the exon 2 region of toll-like receptor 9 (TLR9) gene with susceptibility to systemic lupus erythematosus among Chinese

Abstract: Toll-like receptor 9 (TLR9) plays an important role in the induction and regulation of the innate immune system or adaptive immune responses. Genetic variations within human TLR9 have been reported to be associated with a range of immune-related diseases, such as asthma, systemic lupus erythematosus (SLE) and so on. Family-based association analysis was performed to further investigate whether a single nucleotide polymorphism (rs352140) in the exon 2 region of TLR9 gene is associated with susceptibility to SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
2
25
0
1
Order By: Relevance
“…[27][28][29] In our study, we focused on variants of the TLR9 gene (rs352139 and rs352140) that have previously been associated with SLE. 30 Our study has demonstrated a statistically significant association between MGN and the rs352139 and rs352140 polymorphisms of TLR9, whereby the frequencies of the AA genotype at rs352139 and the GG genotype at rs352140 were significantly higher in MGN patients than in control participants. It is estimated from our results that the A-G haplotype of the TLR9 gene is present in approximately 68.7% of MGN patients.…”
Section: Discussionmentioning
confidence: 50%
“…[27][28][29] In our study, we focused on variants of the TLR9 gene (rs352139 and rs352140) that have previously been associated with SLE. 30 Our study has demonstrated a statistically significant association between MGN and the rs352139 and rs352140 polymorphisms of TLR9, whereby the frequencies of the AA genotype at rs352139 and the GG genotype at rs352140 were significantly higher in MGN patients than in control participants. It is estimated from our results that the A-G haplotype of the TLR9 gene is present in approximately 68.7% of MGN patients.…”
Section: Discussionmentioning
confidence: 50%
“…This increased viral load might serve as a source of TLR9 stimulus in these patients, leading to some of the pathologic findings. MAS is recognized also as a complication of systemic lupus erythematosus (34), a disease that has been linked to TLR9 overstimulation by self DNA (35)(36)(37)(38). Patients with SJIA, another population at risk for MAS, show gene expression profiles consistent with repeated TLR/ IL-1 receptor activation (10).…”
Section: Discussionmentioning
confidence: 99%
“…In particular the T-1237C SNP is associated with an increased risk for asthma in European and American populations (Lazarus et al 2003) and Crohn's disease in a German population (Torok et al 2009). TLR-9 G1635A SNP appears to play a role in susceptibility to SLE (Xu et al 2009) and in relation to renal disease, TLR-9 gene polymorphisms are associated and the histologic severity of disease in Japanese patients with IgA nephropathy (Suzuki et al 2008). …”
Section: Discussionmentioning
confidence: 99%